P35 The responsiveness of spatial and temporal elements of instrumented single-limb balance in those with chronic ankle instability. (17th September 2017) - McKeon, PO; Wikstrom, EA
Abstract : Study Design: Reliability/Responsiveness study. Objectives: To determine the responsiveness of single-limb postural control variables in those with chronic ankle instability (CAI) over 2 weeks without intervention. The variables of interest included the spatial (area of a 95% confidence ellipse) and temporal (average velocity of COP excursions) elements of centre of pressure excursions (COP). Background: Single limb balance assessment using an instrumented force plate is one of the most common assessments of sensorimotor dysfunction associated with CAI. These measures have been used in numerous investigations, but the responsiveness of these measures remains unclear. Methods and Measures: Seventy-seven participants with self-reported CAI participated in this study. CAI was defined in accordance to the International Ankle Consortium guidelines. All participants performed three 10 s trials of single limb balance with eyes open and eyes closed. After a 2 week period, all participants were reassessed. To analyse the spatial and temporal elements of the COP excursions, the area of a 95% confidence ellipse (cm 2 ) and the average resultant velocity (cm/s) were calculated, respectively. The mean of 3 trials in each condition was used for analysis. To analyse the responsiveness, intraclass correlation coefficients (ICC(2, 3) ), the standard error of measure (SEM), and the minimum detectable change (SEM*2 1/2 ) were calculated. Results: The spatial element of COP excursions displayed strong responsiveness (eyes open ICC=0.78, SEM=1.7 cm 2, MDC=1.9 cm 2 ; eyes closed ICC=0.85, SEM=3.9 cm 2, MDC=5.6 cm 2 ). Similarly, the temporal element demonstrated excellent responsiveness (eyes open ICC=0.96, SEM=0.4 cm/s, MDC=0.55 cm/s; eyes closed ICC=0.91, SEM=0.8 cm/s, MDC=1.1 cm/s). Conclusion: Based on the results of this study, both the spatial and temporal elements of COP excursions display excellent responsiveness over time in those with CAI. By understanding the normally occurring error associated with these single-limb balance measures, it is possible to determine the clinical meaningfulness of changes associated with injury and rehabilitation in the CAI population. Changes/differences beyond the MDCs associated with this study may be potentially meaningful.